2015
DOI: 10.1111/opo.12243
|View full text |Cite
|
Sign up to set email alerts
|

Dizziness, but not falls rate, improves after routine cataract surgery: the role of refractive and spectacle changes

Abstract: PurposeTo determine whether dizziness and falls rates change due to routine cataract surgery and to determine the influence of spectacle type and refractive factors.MethodsSelf‐reported dizziness and falls were determined in 287 patients (mean age of 76.5 ± 6.3 years, 55% females) before and after routine cataract surgery for the first (81, 28%), second (109, 38%) and both eyes (97, 34%). Dizziness was determined using the short‐form of the Dizziness Handicap Inventory. Six‐month falls rates were determined us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 47 publications
2
66
0
Order By: Relevance
“…found that, in a population of near‐emmetropic wearers (mean age 32 years), the introduction of unwanted cylindrical errors as small as 0.25 D could be detected by some individuals and that almost all wearers were dissatisfied with spectacles in which cylindrical errors were 0.50 D, with oblique errors having more deleterious effects. Changes in oblique astigmatism have also been found to be associated with increased dizziness in patients after cataract surgery, while the orientation‐dependent spectacle magnification associated with larger, particularly oblique, induced cylinder powers may cause gait and other difficulties . Nevertheless, when considering the possible acceptability of current Alvarez spectacles and their astigmatism from the point of view of safety, it must be remembered that progressive lenses, particularly those with higher additions, show very substantial amounts of astigmatism on either side of the narrow progressive corridor and that the use of such lenses, and of other forms of spectacle multifocal, is accepted, in spite of the higher rates of falls and other problems that older wearers of such lenses experience in comparison with the wear of single‐vision lenses .…”
Section: Discussionmentioning
confidence: 99%
“…found that, in a population of near‐emmetropic wearers (mean age 32 years), the introduction of unwanted cylindrical errors as small as 0.25 D could be detected by some individuals and that almost all wearers were dissatisfied with spectacles in which cylindrical errors were 0.50 D, with oblique errors having more deleterious effects. Changes in oblique astigmatism have also been found to be associated with increased dizziness in patients after cataract surgery, while the orientation‐dependent spectacle magnification associated with larger, particularly oblique, induced cylinder powers may cause gait and other difficulties . Nevertheless, when considering the possible acceptability of current Alvarez spectacles and their astigmatism from the point of view of safety, it must be remembered that progressive lenses, particularly those with higher additions, show very substantial amounts of astigmatism on either side of the narrow progressive corridor and that the use of such lenses, and of other forms of spectacle multifocal, is accepted, in spite of the higher rates of falls and other problems that older wearers of such lenses experience in comparison with the wear of single‐vision lenses .…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion of papers not written in English may have resulted in significant papers being overlooked from this review. The assessment of the extent of the association between dizziness and vision was independently made by several researchers and then agreed upon, but as all were clinical vision scientists (two of which were authors on a recent study included in this review) there may have been a bias towards finding an association rather than the reverse.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, recent research 8,9 has shown that spectacle prescribing can have a measurable and substantial impact on the risk of falls in older adults with cataract. Together, these studies provide valuable direction for how spectacles should be prescribed to minimise risk of falls.…”
mentioning
confidence: 84%
“…In this observational study, 30% of participants switched into multifocals after surgery, providing an opportunity to explore the relationship with fall risk not possible in the Australian study where only few (5%) were prescribed multifocals. In both studies, changes to spectacle prescription were shown to independently impact the occurrence of falls in older people receiving cataract surgery.…”
mentioning
confidence: 97%